Digital media practices as digital border experiences among French cross-border commuters in Luxembourg - Martin, Corinne (Border experiences in Europe: everyday life - working life - communication - languages, 2020)
Keywords: Grenzarbeitnehmer; Medienkonsum; Neue Medien; Pendler; Regionale Mobilität; Saar-Lor-Lux

The Neo-Westphalian Public Sphere of Luxembourg. The Rebordering of a Mediated State Democracy in a Cross-Border Context - Lamour, Christian (Tijdschrift voor economische en sociale geografie, 2017)
Abstract: „The mediatised public sphere in Europe seems to be put at risk by the growing importance attached to commercial values in the Media. At the same time, the Westphalian framework of political publicity is said to be diminishing in scale due to globalisation. However, both affirmations are not necessarily true in cross-border metropolitan regions. As suggested in this paper, based on a quantitative and a qualitative analysis of a free daily publication located in the cross-border urban region of Luxembourg, commercial media can help to reconfigure a neo-Westphalian and territorial public sphere made of linear and network-like borders. It is not so much the source of income of the media and the functional dynamics of international urban areas which determine the future of the mediatised public sphere and its territorial background in borderlands Europe but the values of plural reporters in a changing economic and cultural context.“
Keywords: Medien; Medienkonsum; Presse; Zeitung; Öffentlichkeit